Non-suicidal Self-Injury and Firesetting: Shared and Unique Correlates Among School-Based Adolescents - Tanner, A.; Hasking, Penelope; Martin, G. (Springer New York LLC, 2015)
Distinct behaviors such as non-suicidal self-injury (NSSI) and firesetting may represent functionally equivalent attempts to regulate difficult affective/cognitive or social experiences during adolescence. This study examined possible mechanisms leading to NSSI, as opposed to firesetting, as well as co-occurrence of these behaviors. Participants aged 12–18 years (N = 2,356; 67.5 % female) completed self-report questionnaires measuring NSSI and firesetting, as well as socio-demographic and psychosocial factors including personality traits related to impulsivity and anxiety, negative life events, emotion regulation, and coping. The findings indicated the presence of general risk factors (e.g., negative life events and poor coping) that increase the likelihood that adolescents will engage in any of a range of maladaptive behaviors. The probability of at-risk adolescents engaging in NSSI was increased by psychological states (i.e., rumination and poor self-esteem), whereas socio-demographic and personality traits were associated with firesetting. Implications for prevention and early intervention initiatives are discussed.